Estimation of Impact of Crime the Development on the Human Potential (the Case of Russia’s Regions) - DABIEV, David (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
On the basis of the modified HDI index proposed by the author, the influence of crime rate on the development of human capital in the regions of Russia is estimated. It is shown that the high level of socio-economic development in Russia's regions does not always positively affect the reduction of crime rates, since the high or low crime rate in Russia's regions may be associated with other factors: historical, cultural, etc. We believe that for each region it is necessary to develop its own socio-economic policy aimed at creating conditions for the development of basic socio-cultural attitudes for the harmonious development of society.